A systematic review of self‐report measures of generalized shame. Issue 7 (8th January 2022) - Lear, M. Kati; Lee, Eric B.; Smith, Sarah M.; Luoma, Jason B.
Abstract: Objective: Shame is a transdiagnostic emotion of strong clinical and research interest. Yet, there is a lack of consensus on the definition and varying methods employed across self‐report measures, potentially affecting our ability to accurately study shame and examine whether clinical interventions to alter shame are effective. This paper offers a systematic review of self‐report measures of generalized shame. Methods: PubMed, PsycInfo, and Web of Science were searched. Studies were included when they were available in English and the primary aim was to evaluate measurement properties of scales or subscales designed to measure generalized shame in adults. Results: Thirty‐six papers examining 19 scales were identified, with measures of trait shame more common than state shame. Construct validity, internal consistency, and structural validity were relative strengths. Development and content validity studies were lacking and suffered from low methodological quality. Conclusions: All measures evaluated needed additional research to meet criteria for recommended use.